Write 1 - 2log_{7}x as a single logarithm.
Thanks!
Hi, this kind of problems involves the use of properties. So you want that expression to be simplified in one logarithm.
First, let's write everything as a logarithm. We know that: $\displaystyle log_n (n) = 1$ so we could say that $\displaystyle n = 7$ (in our case). Thus $\displaystyle 1 = log_7 (7)$
Then, we have to put, for the second part, "inside" the logarithm. So we also know that: $\displaystyle a \cdot log_n(x) = log_n(x^a)$. Finally $\displaystyle 2 \cdot log_7(x) = log_7(x^2)$
We put it altogether (using the substraction of logarithm property of the same base) $\displaystyle log_n(x)-log_n(y) = log_n\left(\frac{x}{y}\right)$:
$\displaystyle 1 - 2\cdot log_7(x) = log_7(7) - log_7(x^2) = log_7\left(\frac{7}{x^2}\right)$